2013
DOI: 10.1371/journal.pone.0077024
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in a MicroRNA-502 Minding Site in SET8 Gene Confers Clinical Outcome of Non-Small Cell Lung Cancer in a Chinese Population

Abstract: BackgroundGenetic variants may influence microRNA-target interaction through modulate their binding affinity, creating or destroying miRNA-binding sites. SET8, a member of the SET domain-containing methyltransferase, has been implicated in a variety array of biological processes.MethodsUsing Taqman assay, we genotyped a polymorphism rs16917496 T>C within the miR-502 binding site in the 3′-untranslated region of the SET8 gene in 576 non-small cell lung cancer (NSCLC) patients. Functions of rs16917496 were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 49 publications
4
28
0
1
Order By: Relevance
“…However, no studies have demonstrated a correlation between SET8 and gastric cancer. In this study, we analyzed the association between SET8 expression and gastric cancer risk and outcome, and found that the lower SET8 expression group had a higher survival rate, which is consistent with the data of a previous study Xu et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, no studies have demonstrated a correlation between SET8 and gastric cancer. In this study, we analyzed the association between SET8 expression and gastric cancer risk and outcome, and found that the lower SET8 expression group had a higher survival rate, which is consistent with the data of a previous study Xu et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…SET8 has been shown to be correlated with a series of human tumors, such as hepatocellular cancer, breast cancer, ovarian cancer, and lung cancer (Song et al, 2009;Ding et al, 2012;Guo et al, 2012;Wang et al, 2012;Xu et al, 2013). However, no studies have demonstrated a correlation between SET8 and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rs16917496 in SET8 3'-untranslated region (UTR), a binding site of miR-502, was related to cancer survival. The CC genotype was associated with longer survival time and a decreased risk of death in NSCLC patients (Xu et al, 2013a). Similarly, the CC+CT genotype was closely associated with longer survival of SCLC patients (Ding et al, 2012).…”
Section: Discussionmentioning
confidence: 87%